Corporate brand positioning in the mobile sector in the Czech market - Tang, Yarui; San José Iglesias, Rafael; Šenkárčin, Viktorie; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
The importance of brands has gradually come to the fore as a result of the increasing competition in different markets. In recent years, the mobile industry has significantly impacted people’s daily lives with the development of mobile technology. As competition intensifies, corporate brand positioning has become a crucial strategic tool for companies. This thesis analyzes Xiaomi’s corporate brand positioning in the Czech mobile market and compares it with major competitors: Apple, Samsung, and Huawei. An online survey was conducted to examine consumer perceptions of Xiaomi’s brand associations, identity, and communication channels. The proposed recommendations can assist executives in the mobile industry in improving their marketing strategies and ensure that their brand not only survives but also thrives in the competitive global mobile market.
Vedoucí práce: Rafael San José Iglesias
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses